Prediction of novel putative miRNAs and their targets in buffalo - MISHRA, D C; SMITA, SHUCHI; SINGH, INDRA; DEVI, M NANDHINI; KUMAR, SANJEEV; FAROOQI, M S; CHATURVEDI, K K; RAI, ANIL (The Indian Journal of Animal Sciences, 2017)
MicroRNAs (miRNAs) are 22nt long non-coding RNAs, which regulate the gene regulation at the post transcriptional level in both plants and animals. These miRNA are conserved in nature and hence potential base for new miRNA prediction through homology search. No miRNAs in this species are identified so far in economically important water buffalo (Bubalus bubalis). In this study, EST-based homology search, an established computational approach is used to find the potential miRNAs in buffalo. Six potential miRNA in buffalo were identified utilizing publicly available buffalo ESTs against the already known mature miRNAs of closely related species i.e. Bos taurus. Based on their sequence complementarity, target genes were identified which encode transcription factors (8%), enzymes (30%) and transporters (14%) as well as other proteins involved in physiological and metabolic processes (48%). These target genes also encode the proteins for signal transduction and normal development. This study will accelerate the way for further research on miRNAs and their functions in Bubalus bubalis.